Local organizations for natural resource management: lessons from theoretical and empirical literature - Rasmussen, Lise Nordvig; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 1995)
The sustainability of natural resource management depends not only on appropriate technology and prices, but also upon the institutions involved in resource management at the local level. This discussion paper aims to identify factors which condition local organization for resource management. It draws upon a review of two major bodies of literature: empirical analyses of forestry, fisheries, grazing, and irrigation management, and game theory literature. The empirical literature on resource management highlights the physical and technical characteristics of the resource, the characteristics of the group of users, and the attributes of institutional arrangements as key factors affecting the management capacity of local organizations. Simplistic game theory has often been used to predict a tragedy of the commons for natural resources, but more refined versions provide insights into the role of communication, group size, time horizons, trust, and social norms in supporting collective action. The evidence on voluntary organization indicates that collective management is often a viable alternative to nationalization or privatization of natural resources. Although local organizations will not be able to solve every collective action problem, in many situations they could be at least as effective as other management agencies. Knowledge of the factors which condition local organization should be used to develop policies to support local organizations for natural resource management.